Mitochondria and lipid raft-located FOF1-ATP synthase as major therapeutic targets in the antileishmanial and anticancer activities of ether lipid edelfosine. - Janny A Villa-Pulgarín; Consuelo Gajate; Javier Botet; Alberto Jimenez; Nicole Justies; Rubén E Varela-M; Álvaro Cuesta-Marbán; Ingrid Müller; Manuel Modolell; José L Revuelta; Faustino Mollinedo (Public Library of Science (PLoS), 2017)
Leishmaniasis is the world's second deadliest parasitic disease after malaria, and current treatment of the different forms of this disease is far from satisfactory. Alkylphospholipid analogs (APLs) are a family of anticancer drugs that show antileishmanial activity, including the first oral drug (miltefosine) for leishmaniasis and drugs in preclinical/clinical oncology trials, but their precise mechanism of action remains to be elucidated.Here we show that the tumor cell apoptosis-inducer edelfosine was the most effective APL, as compared to miltefosine, perifosine and erucylphosphocholine, in killing Leishmania spp. promastigotes and amastigotes as well as tumor cells, as assessed by DNA breakdown determined by flow cytometry. In studies using animal models, we found that orally-administered edelfosine showed a potent in vivo antileishmanial activity and diminished macrophage pro-inflammatory responses. Edelfosine was also able to kill Leishmania axenic amastigotes. Edelfosine was taken up by host macrophages and killed intracellular Leishmania amastigotes in infected macrophages. Edelfosine accumulated in tumor cell mitochondria and Leishmania kinetoplast-mitochondrion, and led to mitochondrial transmembrane potential disruption, and to the successive breakdown of parasite mitochondrial and nuclear DNA. Ectopic expression of Bcl-XL inhibited edelfosine-induced cell death in both Leishmania parasites and tumor cells. We found that the cytotoxic activity of edelfosine against Leishmania parasites and tumor cells was associated with a dramatic recruitment of FOF1-ATP synthase into lipid rafts following edelfosine treatment in both parasites and cancer cells. Raft disruption and specific FOF1-ATP synthase inhibition hindered edelfosine-induced cell death in both Leishmania parasites and tumor cells. Genetic deletion of FOF1-ATP synthase led to edelfosine drug resistance in Saccharomyces cerevisiae yeast.The present study shows that the antileishmanial and anticancer actions of edelfosine share some common signaling processes, with mitochondria and raft-located FOF1-ATP synthase being critical in the killing process, thus identifying novel druggable targets for the treatment of leishmaniasis.